The role of bone biomarkers and new imaging techniques in the management of patients with CKD-MBD - Belino,C (2017)
Chronic kidney Disease - Mineral and Bone Disorder (CKD-MBD) encompasses abnormalities in bone turnover, volume and mineralization, compromising bone quantity and quality. Bone biopsy is the gold standard to access bone changes, but is not available in many centers and neither is it included in routine practice. The need for a noninvasive method to evaluate bone disease has promoted the development of multiple bone biomarkers and imaging techniques to assess bone metabolism, to clarify the risk of bone loss and fractures and to guide therapeutic decisions. However, all of these have important limitations and presently no noninvasive method either isolated or in association can replace bone biopsy. This article will discuss the major groups of bone biomarkers and new imaging techniques and their role in CKD-MBD